Conscience and History : A Memoir - McNaught, Kenneth, 1918-1997 (Book collections on Project MUSE., 1999)
"Anyone interested in Canadian academic affairs, history writing, left-wing politics, or Toronto society will find themselves utterly engaged by the witty and urbane voice behind these memoirs of a man who seemed to know simply everyone. Kenneth McNaught's autobiography mixes acute observations on key political issues with memories of his student days in the 1930s, watercolour painting, and summers on Garden Island." "Born in 1918, Kenneth McNaught attended Upper Canada College, North Toronto Collegiate Institute, and the University of Toronto, where he eventually became a history professor. During McNaught's stay at United College of Winnipeg in the 1950s, historian Harry Crowe was dismissed when a private letter critical of the administration found its way into the president's hands. McNaught gives a gripping account of his involvement in this landmark case in the history of academic freedom, which resulted in the development of the Canadian Association of University Teachers, and proved to be his most formative experience. He also discusses his role in the League for Social Reconstruction, the turmoil in the universities in the 1960s, Canada's complicity in Vietnam, the campaign against nuclear war, and his reaction to the growing independence movement in Quebec."--Jacket